Communication infrastructures and the contest over location positioning. (September 2019) - Wilken, Rowan
This article builds on renewed critical awareness of the significance of, and need to understand, the material infrastructures that underpin and, importantly, also sustain mobile communication. The focus of this article is on the fluctuating fortunes of one U.S. company: Skyhook Wireless. The company was founded in 2003 with the explicit aim of exploring and developing systems that responded to a very specific communication infrastructure related challenge: how to calculate location positioning from Wi-Fi signals rather than from cellular towers or by using GPS? In this article, I detail the technical means by which they achieved this, and examine how the strength of Skyhook's position in the field of location positioning and analysis became a key factor driving Google's highly contentious Street View program for extracting and recording Wi-Fi access point and payload data. Through this analysis of Skyhook Wireless and its technical achievements, this article aims to contribute valuable new knowledge to our understanding of the location-related operations of mobile devices; the infrastructures associated with these operations; and the businesses that have emerged around, draw on, contribute to, and have come to dominate, these infrastructural systems.